Endoscopic vacuum-assisted closure therapy for leakage of the lower gastrointestinal tract: multicenter experiences - Book, Thorsten; Engelke, Carsten; Brüggerhoff, Raphael; Winny, Markus; Kraus, Martin; Benecke, Claudia; Zimmermann, Markus; Trostdorf, Ulf; Wedemeyer, Heiner; Marquardt, Jens U.; Voigtländer, Torsten; Wedemeyer, Jochen; Kirstein, Martha M. (Endoscopy International Open, 2023)
Background and study aims Only a few studies are available regarding endoscopic vacuum-assisted closure (E-VAC) therapy for the post-surgery leakage of the lower gastrointestinal tract.Patients and methods In this multicenter German study, we retrospectively analyzed patients treated with E-VAC therapy due to post-surgery leakage of the lower gastrointestinal tract from 2000–2020 at Hannover Medical School, University Medical Center Schleswig-Holstein, Campus Luebeck, and Robert Koch Hospital Gehrden.Results Overall, 147 patients were included in this study. Most patients had undergone tumor resections of the lower gastrointestinal tract (n = 88; 59.9 %). Median time to diagnosis of leakage was 10 days (interquartile range [IQR] 6–19). Median duration of E-VAC therapy was 14 days (IQR 8–27). Increase of C-reactive protein (CRP) levels significantly correlated with first diagnosis of leakage (P < 0.001). E-VAC therapy led to closure or complete epithelialization of leakage in the majority of patients (n = 122; 83.0 %) and stoma reversal was achieved in 60.0 %. Stoma reversal was significantly more often achieved in patients with CRP levels ≤ 100 mg/L at first diagnosis compared to patients with CRP levels > 100 mg/L (78.4 % vs. 52.7 %; P = 0.012). Odds ratio for failure of stoma reversal was 3.36 in cases with CRP values > 100 mg/L (P = 0.017). In total, leakage- and/ or E-VAC therapy-associated complications occurred in 26 patients (17.7 %). Minor complications included recurrent E-VAC dislocations and subsequent stenosis. Overall, 14 leakage- or E-VAC-associated deaths were observed most often due to sepsis.Conclusions E-VAC therapy due to post-surgery leakage of the lower gastrointestinal tract is safe and effective. High levels of CRP are a negative predictor of E-VAC therapy success.